Implementasi Model Pembelajaran Calistung dalam Mengukur Literasi dan Numerasi Melalui Tes AKM untuk Siswa Kelas V di SD Negeri 3 Pengadegan - Damayanti, Rita; Purwati, Panca Dewi (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This research is motivated by the low level of literacy and numeracy among students in class V. Based on observations made in class V, most students have not mastered literacy and numeracy skills well. Therefore, the calistung learning model was chosen which has the advantage of overcoming the difficulties of students who have difficulty reading, writing and arithmetic. The aim of this research is to describe the implementation of the Calistung learning model in measuring literacy and numeracy through the AKM test for fifth grade students at SD Negeri 3 Pengadean. The method in this research is descriptive qualitative with data collection techniques, namely tests, observation and documentation. The research was conducted at SD Negeri 3 Pengadean with 30 class V students as the subject. The research results show that the implementation of the calistung learning model can improve the results of the AKM literacy and numeracy tests. This is evidenced by an increase in the percentage of completion of AKM literacy scores by 46.7% and numeracy by 70% after implementing the calistung learning model. Thus, the implementation of the calistung learning model can improve the AKM literacy and numeracy test results for class V students at SD Negeri 3 Pangadean.